Effectes of Low Frequency Pulsed Magnetic Field on Blood Clotting Time in Male Rabbits - T Ahmad , Dhahir (Diyala Journal of Medicine, 2019)
Background: This research was under taken to estimate the effects of low frequency pulsed magnetic field (LFPMF) on blood clotting time in rabbit males. Aim of this research; The purpose of this study is to evaluate the effects of low frequency pulsed magnetic fields in blood clotting times in male rabbits. Methods: Eight rabbits male were included in this study , four of them were used as a control groups and other four rabbits were used as an exposed groups. They were exposures to six gausses of Low Frequency Pulsed Magnetic Field (LFPMF), at different times (6,12,18,24,30,36,42,48 hours) respectively. Results: The results of this research show that by using compared t-test there was highly significant difference, at period of times (12,18,24,30,36,48hours) of exposure to(LFPMF), between experimental and control groups of male rabbits in clotting time of blood, but there was non significant difference between them in period of times of exposures shown in periodic times(6,42 hours) respectively. Conclusions: The application of low frequency pulsed magnetic fields on blood clotting time, concluded to increasing the blood coagulation time in experimental group of rabbits as compared with control group of rabbits. The mechanism indicated increases in body temperature, ionic exchange, enzymatic and hormonal.